Agglomeration and Location Decision of Foreign Direct Investment (FDI) in Indonesia [Aglomerasi dan Penentuan Lokasi Penanaman Modal Asing (PMA) di Indonesia] - Agustina Agustina; David Flath (Jurnal Ekonomi & Kebijakan Publik, 2019)
Foreign direct investment (FDI) may precipitate remarkable economic growth, even in developing countries. FDI can provide financial resources, transfer technology, improve organizational and managerial practices and skills, and afford access to international markets. This paper aims to measure the relative importance of the different types of agglomeration for location decision of FDI in the manufacturing sector in Indonesia. These data are analyzed with a multinomial logit model where the dependent variable is the choice of location. It examines the determinant factors of new (greenfield) foreign direct investment in the manufacturing sector in Java Island, Indonesia. This study used unpublished micro-level data of principle licenses from the Indonesia Investment Coordinating Board (IICB), which examine 23 counties of Java Island that received manufacturing FDI in the last five years. The finding is agglomeration economies in production (both foreign-owned and domestic firms) show a significant and positive but small impact. Other variables, including facilities, and labor market conditions-anomalously in that a higher minimum wage-matter as much or more than an agglomeration of production. Because the agglomeration effect is small, it means that agglomeration economies are not the detemining factor in attracting FDI. The new foreign investors not only seek counties in which foreign or domestic plants have already located but also consider other things such as the density of roads and the availability of labor. Keywords: agglomeration economies, manufacturing, regional economic activity, multinomial logitAbstrakPenanaman modal asing (PMA) dapat mempercepat pertumbuhan ekonomi yang luar biasa, bahkan di negara-negara berkembang. PMA dapat menyediakan sumber daya keuangan, transfer teknologi, meningkatkan praktik dan keterampilan organisasi dan manajerial, dan memberikan akses ke pasar internasional. Pemerintah Indonesia telah menyadari bahwa PMA dapat memberikan kontribusi yang signifikan terhadap pembangunan ekonomi negara. Paper ini bertujuan untuk mengukur kepentingan relatif dari berbagai jenis aglomerasi untuk penentuan lokasi PMA di sektor manufaktur di Indonesia. Data ini dianalisis dengan model multinomial logit di mana variabel dependen adalah pilihan lokasi. Paper ini meneliti faktor-faktor penentu PMA baru (greenfield) di sektor manufaktur di Pulau Jawa, Indonesia. Penelitian ini menggunakan data tingkat mikro dari izin prinsip yang tidak dipublikasikan dari Badan Koordinasi Penanaman Modal Indonesia (BKPM). Penelitian ini menguji dari 23 kabupaten di Pulau Jawa yang menerima PMA di sektor manufaktur dalam lima tahun terakhir. Hasil dari temuan ekonomi agglomerasi (baik milik asing dan perusahaan domestik) menunjukkan dampak yang signifikan dan positif namun kecil. Variabel-variabel lain, termasuk fasilitas, dan kondisi pasar tenaga kerja-secara anomali dengan upah minimum yang lebih tinggi-menunjukan hasil yang lebih penting dibandingkan aglomerasi. Karena efek aglomerasi yang kecil, hal ini berarti bahwa ekonomi aglomerasi bukanlah faktor penentu dalam menarik PMA. Investor asing yang baru tidak hanya mencari kabupaten di mana pabrik asing atau domestik telah berada tetapi juga mempertimbangkan hal-hal lain seperti kepadatan jalan dan ketersediaan tenaga kerja.Kata kunci: ekonomi aglomerasi, industri, ekonomi regional, multinomial logit